Examination of valuable ingredients of some wild fruits - Sipos, B. Z.; Szabó, N.; Stéger-Máté, M.; Schmidt, G. (International Journal of Horticultural Science, 2002)
A possible way of the development of Hungarian agriculture is the selection and growing of new fruit species and varieties featuring special qualities, with high biological nutritive and health protecting properties due to their natural composition. A reserve for such new fruits is the native dendroflora, e.g. those wild-growing trees and shrubs of Hungary, which bear edible fruits. The publication is giving a summary of chemical analyses done on the fruits of the plants listed below. The research team on the project started the work in 2001 with woody species (genera) as follows: • common elder (Sambucus nigra) clone named Szcs-1, Szcs-2, Szcs-3, Szcs-4, Szcs-5, SzcsK-1, SzcsK-2 • dog rose (Rosa canina) types: clones named Sz-1, Sz-2, Sz-3, Sz-4 and Sz-5 . • native rowans: Sorbus dacica, S.rotundifolia, S. degenu, S.bakonyensis cv. Fánivölgy • hawthorns: Crataegus monogyna, C. orientalis,C..v lavallei. • cornel cherry: Cornus mas cv. Császló. The present paper is reporting on the content of the following compounds in the fruits: dry matter (refractometric values), total acid content, ascorbic acid, 13-carotene, pectin, minerals and carbohydrates. The results have shown that these wild fruits have excellent composition. Besides their curative effects, their content of minerals, ascorbic acid and 13-carotene has surpassed that of the traditional fruits. These fruits are rich in ascorbic acid, 13-carotene and pectin. The high content of the above-listed, biologically active compounds makes the new wild fruits studied suitable for the preparation (and later: mass-production) of special curative and exclusive products.